Higher order networked sliding mode controller for heat exchanger connected via data communication network. (March 2021) - Shah, Dipesh; Shah, Ankit; Mehta, Axaykumar
Abstract: Heat Exchanger (HE) is a widely used device in industrial applications for both cooling and heating processes because it can sustain a wide range of temperature and pressure parameters without affecting the output performance of the system. In this paper, we propose a Higher-Order Sliding Mode (HOSM) controller for HE connected via a data communication network. The higher-order sliding mode controller is well known for chattering attenuation which occurs due to switching control action in a sliding mode control technique. The HOSM controller based on super-twisting algorithm is proposed to compensate for the random communication network delay and process delay in the presence of model uncertainties of HE. The sufficient condition for stability is ensured by the trivial Lyapunov function. The simulation results demonstrate the efficacy of the designed controller for the HE in terms of chattering, delay compensation, and faster convergence. Further, the performance of HE is compared in two ways. In first case, the proposed controller performance is compared for a HE system with network delay and without network delay. In the second case, the performance of the proposed controller is compared with the conventional constant plus proportional rate reaching law based controller.